Detection of Escherichia coli, rotavirus, and Cryptosporidium spp. from drinking water, kitchenware, and flies in a periurban community of Lusaka, Zambia. (8th June 2022) - Asada, Yasuhiro; Chua, Min Li; Tsurumi, Mayu; Yamauchi, Taro; Nyambe, Imasiku; Harada, Hidenori
Abstract: Fecal contamination with a poor water, sanitation and hygiene environment in urban informal settlements poses diarrhea risks. Little information is available on the contamination of environmental media with enteric pathogens in such settlements. We investigated the contamination of Escherichia coli, rotavirus, and Cryptosporidium spp. in water, on kitchenware, and on flies in urban informal settlements of Chawama and Kanyama, Lusaka, Zambia. These environmental media were examined by XM-G agar cultivation for E. coli and specific real-time RT-PCR assays to detect rotavirus and Cryptosporidium spp. E. coli ; rotavirus, and Cryptosporidium spp. were detected in samples of household stored drinking water (6 of 10 samples, 3 of 10 samples, and 2 of 10 samples, respectively), cups (10 of 20 samples, 2 of 13 samples, 1 of 13 samples, respectively), and flies (35 of 55 samples, 5 of 17 samples, 1 of 17 samples, respectively). The ranges of rotavirus concentrations in household stored drinking water, on cups, and flies were 2.9 × 10 2 –2.2 × 10 5 copies/L, 1.2 × 10 2 –4.3 × 10 2 copies/cup, and 5.0 × 10 1 –2.0 × 10 2 copies/fly, respectively. These results indicate the contribution of drinking water and kitchenware to enteric pathogen exposure and potential role of flies in microbial transmission. HIGHLIGHTS: The study was conducted in a periurban informal settlement of sub-Saharan Africa. Rotavirus and Cryptosporidium spp. were detected from point-of-use drinking water. These two pathogens were also detected from drinking cups and flies. People are exposed to these enteric pathogens from drinking water as well as cups. The results imply the role of flies as a vector of these enteric pathogens. Graphical Abstract